Project-Based Learning Via Traditional Game in Physics Learning: Its Impact on Critical Thinking, Creative Thinking, and Collaborative Skills - N. Khoiri; S. Ristanto; A. F. Kurniawan (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This study aims to investigate how PjBL via traditional games impact students’ critical thinking, creative thinking, and collaborative skills. The research sample is a local school in Semarang. The research design was a quantitative study using the pre-experimental design type one group pretest-posttest method. There is only one predetermined group in this design. The theme of the game that the project will create was revealed following the pre-test. The research results show students’ creative thinking skills in applying the PjBL model via game techniques are 61.53% in high criteria and 38.46% in medium criteria. The study results also show a fair increase in the N-Gain value for the four indicators of creative thinking skills: improvisation, elaboration, creativity, vision, effectiveness, and efficiency. The results show it is effective for six students (25%), fairly effective for 13 students (54.16%), and less effective for five students (20.83%). The study’s results also show that the Mann-Whitney U statistical test is 69. It means that the PjBL model impacts students’ collaborative skills. This research has a big impact on increasing students’ creative thinking skills and collaboration.